Pre-hospital severe traumatic brain injury – comparison of outcome in paramedic versus physician staffed emergency medical services - Pakkanen, Toni (Scand J Trauma Resusc Emerg Med, 2016)
BACKGROUND: Traumatic brain injury (TBI) is one of the leading causes of death and permanent disability. Emergency Medical Services (EMS) personnel are often the first healthcare providers attending patients with TBI. The level of available care varies, which may have an impact on the patient’s outcome. The aim of this study was to evaluate mortality and neurological outcome of TBI patients in two regions with differently structured EMS systems. METHODS: A 6-year period (2005 – 2010) observational data on pre-hospital TBI management in paramedic-staffed EMS and physician-staffed EMS systems were retrospectively analysed. Inclusion criteria for the study were severe isolated TBI presenting with unconsciousness defined as Glasgow coma scale (GCS) score ≤ 8 occurring either on-scene, during transportation or verified by an on-call neurosurgeon at admission to the hospital. For assessment of one-year neurological outcome, a modified Glasgow Outcome Score (GOS) was used. RESULTS: During the 6-year study period a total of 458 patients met the inclusion criteria. One-year mortality was higher in the paramedic-staffed EMS group: 57 % vs. 42 %. Also good neurological outcome was less common in patients treated in the paramedic-staffed EMS group. DISCUSSION: We found no significant difference between the study groups when considering the secondary brain injury associated vital signs on-scene. Also on arrival to ED, the proportion of hypotensive patients was similar in both groups. However, hypoxia was common in the patients treated by the paramedic-staffed EMS on arrival to the ED, while in the physician-staffed EMS almost none of the patients were hypoxic. Pre-hospital intubation by EMS physicians probably explains this finding. CONCLUSION: The results suggest to an outcome benefit from physician-staffed EMS treating TBI patients. TRIAL REGISTRATION: ClinicalTrials.gov ID NCT01454648